PENGENDALIAN PENYAKIT CVPD PADA TANAMAN JERUK DAN PENYAKIT KARAT PURU PADA TANAMAN ALBESIA DI DESA TARO - WIJAYA, I N. (Buletin Udayana Mengabdi; Vol 8 No 1 (2009): Volume 8 No.1 – April 2009, 2012)
ABSTRACT The activities of the Community Service was conducted for the farmer group in Taro village, Gianyar regency on 16 th July until 4 th October 2008. The aim was to improve soft skill of the farmer group in CVPD disease at citrus plant and rust gall disease at albesia plant. The activities was attended by 97 participants from local farmer group of Taro village. The methods used in activities were lecture, demontration and practice in the citrus field and albesia field. All participants seemed to be very serious to listen to since the topic or theme was still rare for them. The participants were enthusiastic to participate in all activities and hope for the team of Unud be able to come again with new information.